Analysis of Productivity and Comparative-Competitive Advantage of MSMEs in Gorontalo City - Indriyati Lanangawa; Mohammad Zubair Hippy; Siti Rahmatia Machieu; Dian Rahayu Maku; Mustakim Mokoginta; Djunaida Kandow; Meilan Daud (Citakonsultindo, 2026)
MSMEs play a strategic role in the local economy, but in Gorontalo City, their productivity and sectoral advantages show a complex dynamic and have not optimally supported the transformation towards a service-based city. This study aims to analyze the productivity and comparative and competitive advantages of MSMEs in Gorontalo City, as well as to map potential sectors for future development. The research uses a mixed-method approach with an explanatory sequential design, where quantitative analysis of productivity data from 2014–2024 and projections for 2025–2030 is conducted using dynamic system modeling with Vensim, as well as regression, exponential smoothing, and ARIMA methods. Sectoral advantage analysis is carried out using the LQShare and LQShift approaches, which are dynamic in nature. The results show that MSME productivity experienced fluctuations and a decline due to the pandemic, but began to recover in 2024 and is projected to increase in an optimistic scenario along with digitalization policies and strengthening the service sector. The LQ analysis identifies the garment and handicraft sectors as progressive, while the metal-electronics sector remains sluggish, and the building materials and food sectors fall under the developing category. The study recommends strengthening local fiscal policies, improving MSME digital literacy, developing an e-commerce ecosystem, and business incubation for the developing and sluggish sectors. These efforts are expected to strengthen MSME productivity sustainably and support the vision of Gorontalo City as a service economy hub in 2025–2029.